The Effect of Socio-Critical and Problem-Oriented Approaches on Students' Critical Thinking Skills in Green Chemistry Learning - Kamila, Putri Diana; Erlina,; Sahputra, Rachmat (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Critical thinking skills play an essential role in enabling students to understand scientific concepts and solve problems logically and reflectively. However, the 2022 PISA results indicate that Indonesian students still demonstrate low performance in this area, particularly in chemistry learning, which often emphasizes memorization rather than reasoning. This study aims to analyze the effect of an integrated Socio-Critical and Problem-Oriented approach on students’ critical thinking skills in green chemistry learning at State Senior High School 1 Sintang. This research employed a quantitative method with a pre-experimental One Group Pretest–Posttest Design involving 30 students from class XC. Data were collected through classroom observations and critical thinking tests covering five indicators: interpretation, analysis, evaluation, inference, and explanation, and were analyzed using normality tests, homogeneity tests, and t-tests. The findings reveal a significant improvement in students’ critical thinking skills after the implementation of the integrated approach. These results indicate that embedding socio-scientific and contextual environmental issues within problem-oriented green chemistry learning effectively enhances students’ critical thinking skills at the senior high school level.